UNDERSTANDING THE LINK BETWEEN LOGISTICS TECHNOLOGY, PERFORMANCE, AND COMPETITIVE ADVANTAGE IN THAILAND’S THIRD-PARTY LOGISTICS SECTOR (Journal of Technology and Operations Management, 2025)
In Thailand, third-party logistics (3PL) companies operate at a loss of 35 percent, indicating their inability to compete with other logistics service providers. Due to technology being one of the factors involved, the objective of this study aims to investigate the relationship between logistics technology, logistics performance, and competitive advantage in small third-party logistics (3PL) enterprises in Thailand. This study used partial least squares structural equation modelling (PLS-SEM) as a statistical approach for data analysis. The sample size was 159 respondents, who are small 3PL enterprises in three southern border provinces of Thailand. The finding indicated that logistics technology has a positive relationship with logistics performance and competitive advantage of 3PL in Thailand. Moreover, logistics performance, as a mediating factor is linked to logistics technology and competitive advantage. This study could be beneficial for the 3PL firms for improving technology in logistics operations, thereby achieving better outcomes and success in company competition.